The Prospects for Future Economic Growth in the Euro Area - Kieran McQuinn; Karl Whelan (Intereconomics, 2016)
With a long-term projection of TFP growth of 0.2 per cent, a gradual decline in the work-age population and a static average workweek, we project a "baseline" average real GDP growth rate in the euro area of just 0.6 per cent over the next decade — even if the unemployment rate and investment share of GDP return to their pre-crisis levels by 2020.
Keywords: 330